Silicon-containing thermal paste

CN116761844BActive Publication Date: 2026-10-27WACKER CHEMIE AG
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202280012447.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-01-29
Filing Date
2022-01-13
Publication Date
2026-10-27
Estimated Expiration
2042-01-13

Smart Images

  • Figure CN116761844B_ABST
    Figure CN116761844B_ABST
Patent Text Reader

Abstract

The invention relates to a crosslinkable heat conductive silicone composition (Y) comprising: 5-50 vol.-% of a crosslinkable silicone composition (S), and 50-95 vol.-% of at least one heat conductive filler (Z) having a thermal conductivity of at least 5 W / mK, with the proviso that the crosslinkable heat conductive silicone composition (Y) has a thermal conductivity of at least 0.6 W / mK and at least 20 vol.-% of metal silicon particles are comprised as heat conductive filler (Z) which fulfill the following characteristics: a) their average diameter x50 is in the range of 30-150 pm; b) they are mainly round and characterized by a ratio of width / length (aspect ratio w / l) of at least 0.76; c) their distribution width SPAN ((x90-x10) / x50) is at least 0.40; d) they comprise at most 1.5 wt.-% of silicon particles smaller than 2 pm. The invention also relates to its production and its use.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention relates to thermally conductive silicone compositions, and to their production and use. Background Technology

[0002] In the automotive and electronics industries, thermally conductive silicone compositions are widely used for thermal management. Important examples include thermally conductive adhesives, thermally conductive pads, gap fillers, and encapsulation compounds. Of the applications mentioned, gap fillers for lithium-ion batteries in electric vehicles are by far the largest in terms of volume. Gap fillers are thermally conductive elastomers that completely and sustainably fill air gaps caused by manufacturing tolerances, differences in build height, or varying coefficients of thermal expansion, minimizing thermal resistance, for example, between electronic components and cooling jackets or heat sinks.

[0003] Existing technologies include various thermally conductive fillers added to silicone to increase its thermal conductivity. However, these all have significant drawbacks. Ceramic fillers, such as alumina, have very high density and therefore significantly increase the weight of the component. Furthermore, they are relatively expensive. Metallic fillers, such as aluminum or silver powder, are conductive, which is unacceptable for many applications. Many metals and alloys are also relatively expensive.

[0004] Many other fillers with high thermal conductivity, such as carbon nanotubes, boron nitride, and aluminum nitride, may also be used only to a limited extent, or in small quantities or for specific applications, due to their relatively high cost.

[0005] Existing technologies include various thermally conductive silicone compositions containing silicon particles as thermally conductive fillers. These are relatively lightweight and inexpensive. Furthermore, silicon, as a semiconductor, has extremely low electrical conductivity. However, silicon particles according to existing technologies are unsuitable for use as interstitial fillers in lithium-ion batteries for electric vehicles.

[0006] The silicon particles used in the prior art are typically obtained through grinding. A drawback is that these particles have a high surface area and bind a very large amount of polymer. This significantly increases the viscosity of the silicone composition. It is possible to produce only mixtures with relatively low filler levels and low thermal conductivity. At higher filler levels, the composition becomes very rigid and can no longer be processed by conventional methods (e.g., dispensers). Silicone compositions containing ground silicon particles have also been found to have relatively high flammability.

[0007] Using silicon particles smaller than 20 μm is disadvantageous because such small particles have relatively low minimum ignition energy and therefore pose a dust explosion hazard, requiring complex and expensive safety precautions in industrial processing.

[0008] JP2019131669A2 teaches the use of metallic Si particles with a size of 0.1–200 μm and an electrically insulating coating as a thermally conductive filler for siloxane-free organic resins. These particles can be produced by thermal decomposition, melting, or grinding methods, or obtained from polishing or grinding methods. In a separate process step, the particles are provided with an electrically insulating coating. In an example, JP2019131669A2 discloses an organic resin containing up to 65% by volume of ground Si particles with an average particle size of 32 μm and a thermal conductivity as high as 7 W / mK. A disadvantage is the use of ground particles with relatively high flammability. The disclosed cured rubber is inelastic and therefore unsuitable for use as a gap filler in lithium-ion batteries.

[0009] US2016122611 teaches a conductive and thermally conductive silicone elastomer composition comprising a thermally conductive filler of less than 30 μm, more preferably 2 to 8 μm, in combination with carbon black. The thermally conductive filler may be silicon powder. The examples disclosed are compositions comprising up to 60 wt% of ground Si particles having an average particle size of 5 μm or up to 46 wt% of ground Si particles having an average particle size of 40 μm. The composition has a thermal conductivity up to 1.0 W / mK. A disadvantage is the use of ground particles, which have relatively high flammability and only allow for compositions with relatively low filler levels and low thermal conductivity.

[0010] US2007135555 teaches thermally crosslinked, thermally conductive silicone compositions containing spherical or milled metallic Si particles produced by a melt process, each having an average particle size of up to 100 μm, more preferably 2 to 25 μm. Examples disclose compositions comprising up to 71 wt% milled Si particles with an average particle size of 12 μm or up to 71 wt% spherical Si particles with an average particle size of 5 μm, each combined with an oxide filler (e.g., Fe₂O₃ or Al₂O₃). These compositions have thermal conductivity up to 1.2 W / mK. A disadvantage is the use of very small Si particles, which are relatively highly flammable and only allow for compositions with relatively low filler levels and low thermal conductivity.

[0011] US2007117920 teaches thermally crosslinked, thermally conductive silicone compositions comprising spherical or ground metallic Si particles having an average particle size of 2 to 100 μm, more preferably 2 to 25 μm. Examples disclose compositions comprising up to 67% by weight of ground Si particles having an average particle size of 5 to 12 μm as the sole filler or in combination with Al₂O₃. The viscosity of the mixture ranges from 30,000 mPa·s to 260,000 mPa·s at thermal conductivity up to 1.0 W / mK. A disadvantage is the use of very small Si particles, which are relatively highly flammable and only allow for compositions with relatively high viscosity, low filler levels, and low thermal conductivity.

[0012] US2001051673 teaches a thermally crosslinked, thermally conductive silicone elastomer composition containing sheet-like particles with an average particle size of 0.1-350 μm or spherical particles, preferably sheet-like, composed of a magnetic silicon-containing Fe-Si alloy with an average particle size of 0.1-50 μm, preferably 0.5-20 μm. The examples disclose a composition comprising 30 vol% spherical Fe-Si particles and 40 vol% Al₂O₃ particles, these particles consisting of 97 wt% Fe and 3 wt% Si, with an average particle size of 8 μm. The thermal conductivity is 4.0 W / mK. A disadvantage is the use of very small Fe-Si particles with a very high iron content. As a result, these particles are electrically conductive, have a relatively high density, and are relatively highly flammable. Another disadvantage is the use of a large amount of Al₂O₃, which means the composition has a very high density.

[0013] US 4292223 teaches a crosslinkable, thermally conductive silicone elastomer composition containing metal particles (e.g., silicon, preferably an alloy, having an average particle size of 40 μm to 300 μm). These particles can be spherical or irregular in shape, with an aspect ratio up to 8 (corresponding to an aspect ratio (w / l) of not less than 0.125 according to ISO 9276-6). This leads to a very broad definition of possible particle forms, as these particles can be spherical (corresponding to an aspect ratio of 1) or rod-shaped (where the length can be 8 times greater than the width). A composition containing 28% by weight of ground Si particles with an average particle size of 44 μm is disclosed, but a w / l ratio is not disclosed. The disadvantage is the use of relatively highly flammable ground particles. Furthermore, the ground particles have a relatively high surface area, and therefore compositions containing ground particles have relatively high viscosity and are difficult to handle. The crosslinked material has low flexibility and is brittle.

[0014] US2006228542 describes a thermally conductive elastomer containing two different sizes of thermally conductive fillers. The elastomer can be silicone, etc. The first thermally conductive filler is formed of an electrically insulating and thermally conductive ceramic. As one of several examples of suitable ceramic materials, "silicone" is incorrectly listed instead of "silicon dioxide." However, it is perfectly clear to those skilled in the art upon reading this disclosure that it actually means silicon dioxide ceramic, since silicon metal is not ceramic, but fused silica ceramic (i.e., SiO2 ceramic) is well known. The first thermally conductive filler also has a unimodal distribution and an average particle size of at least 20 μm. It is disclosed that the first filler particles are spherical or round and can also be hollow. It has a preferred average particle size of 30 to 95 μm and a standard deviation of 15 to 40 μm. This is a very nonspecific definition of the possible distribution range, and therefore these particles can have a very narrow or very wide distribution.

[0015] This is illustrated by the following observation: a standard deviation of 40 μm and an average particle size of 30 μm correspond to a very wide particle size distribution, while a standard deviation of 15 μm and an average particle size of 95 μm correspond to a very narrow particle size distribution. There is no teaching in US2006228542 regarding the effect of the standard deviation of the filler's particle size distribution on the properties of the elastomer.

[0016] Therefore, the object of the present invention is to provide a thermally conductive silicone elastomer composition that does not exhibit the aforementioned disadvantages of the prior art, and that combines low density, low cost and high thermal conductivity.

[0017] This objective is achieved by the crosslinkable thermally conductive silicone composition (Y) of the present invention, which comprises relatively large Si particles having an average particle size of 30 μm to 150 μm, being primarily spherical, and simultaneously having a particularly large or wide particle size distribution. Completely unexpectedly, these silicone compositions (Y) of the present invention were found in experiments to exhibit significantly reduced flammability.

[0018] In the context of this invention, "primarily circular" Si particles should be understood to refer to those with a spherical to elliptical shape and a smooth surface. They may also be referred to as potato-shaped. Figure 1 The present invention illustrates the primarily circular shape of these Si particles, as exemplified by examples. Non-inventory Si particle shapes are characterized by having "splashed" particles. Figure 2 , containing nodular particles Figure 3 and particles with "horns" and "sharps". Figure 4 As shown. Therefore, the metallic Si particles of the present invention are not sputtered, nodular, angular, or sharp. However, they may contain such particles to a degree of impurity without compromising the inventive effect.

[0019] according to Figures 1 to 4 The properties of the Si particles are shown in the table below.

[0020] 1 98 0.84 0.87 Invention 2 38 0.68 0.70 This is not the invention. 3 73 0.67 0.72 This is not the invention. 4 37 0.67 0.76 This is not the invention.

[0021] This invention provides a crosslinkable thermally conductive silicone composition (Y) comprising:

[0022] 5-50% by volume of crosslinkable silicone composition (S), and

[0023] 50%-95% by volume of at least one thermally conductive filler (Z) having a thermal conductivity of at least 5 W / mK, provided that

[0024] The crosslinkable thermally conductive silicone composition (Y) has a thermal conductivity of at least 0.6 W / mK, and

[0025] At least 20% by volume of metallic silicon particles present as thermally conductive filler (Z) satisfy the following characteristics:

[0026] a) Their average diameter x50 is in the range of 30–150 μm;

[0027] b) They are primarily circular and are characterized by a width-to-length ratio (aspect ratio w / l) of at least 0.76;

[0028] c) Their distribution range SPAN((x90-x10) / x50) is at least 0.40;

[0029] d) They contain up to 1.5% by weight of silicon particles smaller than 2 μm.

[0030] In the context of this invention, the terms "thermal conduction" and "thermal conductivity" are equivalent.

[0031] In the context of this invention, thermally conductive filler (Z) should be understood to mean any filler having a thermal conductivity of at least 5 W / mK.

[0032] In the context of this invention, thermally conductive silicone composition (Y) should be understood to refer to those silicone compositions that significantly exceed the thermal conductivity (typically about 0.2 W / mK) of polydimethylsiloxane without fillers and additives, characterized in that they have a thermal conductivity of at least 0.6 W / mK.

[0033] In the context of this invention, all parameters describing particle size (parameter: average diameter x 50), particle size distribution (parameters: standard deviation σ and distribution range SPAN), or particle shape (parameters: aspect ratio w / l and sphericity SPHT) are based on volume distribution. The indices mentioned can be determined, for example, by dynamic image analysis according to ISO 13322-2 and ISO 9276-6, using, for example, the Camsizer X2 from Retsch Technology.

[0034] Those skilled in the art will understand that standard deviation is not standardized, and it is only a feasible characteristic for evaluating the particle size distribution of different samples when the average particle size of the compared samples is approximately the same. Therefore, in the context of this invention, to describe the relative width of the particle size distribution, a particle size distribution range weighted by median particle size x 50 is used, and the dimensionless distribution range SPAN is defined as:

[0035] SPAN = (x90 - x10) / x50.

[0036] Aspect ratio is used as an index to describe particle shape. Earlier prior art frequently described aspect ratio as the ratio of length to width (l / w). This results in a value not less than 1. In more recent literature, such as according to ISO 9276-6, aspect ratio is calculated from the inverse ratio of width to length (w / l). This results in a value not greater than 1. These two indices can be converted to each other by forming inverses. In the context of this invention, aspect ratio is defined as the ratio of particle width to length (w / l). Particle width is hereby defined by X. c min Given that this is the smallest of all the maximum chords measured in the particle projection, and the particle length is given by X. Fe max The given value is the longest Feret diameter among all Feret diameters measured in the particle. More detailed information can be found, for example, in "Operating Instructions / Manual Particle Size Analysis System". "Retsch Technology GmbH, 42781 Haan; Doc. No. CAMSIZER V0115. This leads to the following aspect ratio formula: "

[0037] w / l=X c min / X Fe max

[0038] The sphericity SPHT is calculated using the following formula from the area A of the projected area of ​​the particle being analyzed relative to the area of ​​a circle with the same perimeter P having the projected particle (more detailed information can be found, for example, in "Operating Instructions / Manual Particle Size Analysis System"). ”, Retsch Technology GmbH, 42781Haan; Doc.No.CAMSIZER V0115):

[0039] SPHT = 4πA / P 2

[0040] The index SPHT corresponds to the square of the roundness C according to ISO 9276-6.

[0041] In order to avoid creating too many pages in the description of this invention, preferred embodiments of individual features will be described in detail below.

[0042] However, expert readers will clearly understand this disclosure method, which therefore also clearly discloses and explicitly desires any combination of different preference levels.

[0043] Crosslinkable silicone composition (S)

[0044] As a crosslinkable silicone composition (S), it is possible to use silicones known to those skilled in the art from the prior art, such as addition crosslinking, peroxide crosslinking, condensation crosslinking, or radiation crosslinking silicone compositions (S). Addition crosslinking or peroxide crosslinking silicone compositions (S) are preferred.

[0045] Peroxide-crosslinked silicone compositions (S) are well known to those skilled in the art. In their simplest form, they contain at least one organopolysiloxane having at least two crosslinkable groups (e.g., methyl or vinyl) per molecule, and at least one suitable organic peroxide catalyst. If the composition according to the invention is crosslinked by free radicals, the crosslinking agent used is an organic peroxide that serves as a source of free radicals. Examples of organic peroxides are acyl peroxides, such as dibenzoyl peroxide, bis(4-chlorobenzoyl) peroxide, bis(2,4-dichlorobenzoyl) peroxide, and bis(4-methylbenzoyl) peroxide; alkyl peroxides and aryl peroxides, such as di-tert-butyl peroxide, 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane, dicumyl peroxide, and 1,3-bis(tert-butylperoxyisopropyl)benzene; perketals, such as 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane; and peresters, such as diacetylperoxydicarbonate, tert-butyl perbenzoate, tert-butyl peroxyisopropyl carbonate, tert-butyl peroxyisononanoate, dicyclohexyl peroxydicarbonate, and 2,5-dimethylhexane-2,5-diperbenzoate.

[0046] One type of organic peroxide may be used; it is also possible to use a mixture of at least two different types of organic peroxides.

[0047] The addition-crosslinked silicone composition (S) is particularly preferred.

[0048] The addition-crosslinking silicone composition (S) used according to the present invention is known in the prior art and, in its simplest case, contains...

[0049] (A) At least one straight-chain compound having a group containing an aliphatic carbon-carbon double bond,

[0050] (B) At least one linear organopolysiloxane having Si-bonded hydrogen atoms,

[0051] Alternatively, instead of (A) and (B),

[0052] (C) At least one linear organopolysiloxane having SiC-bonded groups containing aliphatic carbon-carbon multiple bonds and Si-bonded hydrogen atoms, and

[0053] (D) At least one hydrogenation silanization catalyst.

[0054] The addition-crosslinked silicone composition (S) can be a one-component silicone composition or a two-component silicone composition.

[0055] In the two-component silicone composition (S), the two components in the addition-crosslinked silicone composition (S) according to the invention may contain any combination of all components, typically provided that one component does not simultaneously contain a siloxane having aliphatic multiple bonds, a siloxane having Si-bonded hydrogen, and a catalyst, i.e. substantially not simultaneously contain components (A), (B), and (D) or (C) and (D).

[0056] As is well known, compounds (A) and (B) or (C) used in the addition-crosslinking silicone composition (S) according to the invention are selected to make crosslinking possible. For example, compound (A) has at least two aliphatic unsaturated groups and (B) has at least three Si-bonded hydrogen atoms, or compound (A) has at least three aliphatic unsaturated groups and siloxane (B) has at least two Si-bonded hydrogen atoms, or, instead of compounds (A) and (B), siloxane (C) having aliphatic unsaturated groups and Si-bonded hydrogen atoms in the above-described ratio is used. A mixture of (A), (B), and (C) having the above-described ratio of aliphatic unsaturated groups and Si-bonded hydrogen atoms is also possible.

[0057] The addition-crosslinked silicone composition (S) according to the invention typically comprises 30-99.0% by weight, preferably 40-95% by weight, and more preferably 50-90% by weight (A). The addition-crosslinked silicone composition (S) according to the invention typically comprises 1-70% by weight, preferably 3-50% by weight, and more preferably 8-40% by weight (B). If the addition-crosslinked silicone composition according to the invention includes component (C), then based on the total amount of the addition-crosslinked silicone composition (S) according to the invention, there is typically at least 30% by weight, preferably at least 45% by weight, and more preferably at least 58% by weight (C).

[0058] The compound (A) used according to the present invention may comprise a silicon-free organic compound preferably having at least two aliphatic unsaturated groups, and an organosilicon compound preferably having at least two aliphatic unsaturated groups, or a mixture thereof.

[0059] Examples of silicone-free organosilicone compounds (A) are 1,3,5-trivinylcyclohexane, 2,3-dimethyl-1,3-butadiene, 7-methyl-3-methylene-1,6-octadiene, 2-methyl-1,3-butadiene, 1,5-hexadiene, 1,7-octadiene, 4,7-methylene-4,7,8,9-tetrahydroindene, methylcyclopentadiene, 5-vinyl-2-norbornene, bicyclo[2.2.1]hepta-2,5-diene, 1,3-diisopropenylbenzene, vinyl-containing polybutadiene, 1,4-divinylcyclohexane, 1,3,5-trienylbenzene, 1,3,5-trivinylbenzene, 1,2,4-trivinylcyclohexane, 1,3,5-triisopropenylbenzene, 1,4-divinylbenzene, 3-methyl-1,5-heptadiene, 3 -Phenyl-1,5-hexadiene, 3-vinyl-1,5-hexadiene and 4,5-dimethyl-4,5-diethyl-1,7-octadiene, N,N'-methylenebisacrylamide, 1,1,1-tris(hydroxymethyl)propane triacrylate, 1,1,1-tris(hydroxymethyl)propane trimethacrylate, tripropylene glycol diacrylate, diallyl ether, diallylamine, diallyl carbonate, N,N'-diallylurea, triallylamine, tris(2-methylallyl)amine, 2,4,6-triallyloxy-1,3,5-triazine, triallyl-s-triazine-2,4,6(1H,3H,5H)-trione, diallyl malonate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, poly(propylene glycol) methacrylate.

[0060] The addition-crosslinked silicone composition (S) according to the invention preferably contains at least one aliphatic unsaturated organosilicon compound as component (A). It is possible to use any aliphatic unsaturated organosilicon compound used to date in addition-crosslinked compositions, such as silicone block copolymers having urea segments, silicone block copolymers having amide segments and / or imide segments and / or esteramide segments and / or polystyrene segments and / or silanthracene segments and / or carborane segments, and silicone graft copolymers having ether groups.

[0061] The organosilicon compound (A) used, which has SiC-bonded groups with aliphatic carbon-carbon multiple bonds, is preferably a straight-chain or branched organopolysiloxane composed of units of general formula (I).

[0062] R 4 a R 5 b SiO (4-a-b) / 2 (I)

[0063] in

[0064] R 4Independently, they are the same or different organic or inorganic groups that do not contain aliphatic carbon-carbon double bonds.

[0065] R 5 Independently, they are the same or different hydrocarbon groups, monovalent, substituted or unsubstituted, SiC-linked, and having at least one aliphatic carbon-carbon multiple bond.

[0066] a is 0, 1, 2, or 3, and

[0067] b is 0, 1, or 2.

[0068] The conditions are that the sum of a+b does not exceed 3 and each molecule has at least 2 R. 5 Group.

[0069] R 4 The groups can be monovalent or polyvalent, wherein these polyvalent groups, such as divalent, trivalent or tetravalent groups, can then be linked together with multiple, such as two, three or four siloxy units of formula (I).

[0070] R 4 Other examples are monovalent groups -F, -Cl, -Br, and OR. 6 -CN, -SCN, -NCO, and SiC-bonded, substituted or unsubstituted hydrocarbon groups (which can be interrupted by an oxygen atom or a -C(O)- group), and divalent groups bonded to Si at either end according to formula (I). If R 4 If the group includes a SiC-bonded substituted hydrocarbon group, then the preferred substituents are halogen atoms, phosphorus-containing groups, cyano groups, and -OR groups. 6 -NR 6 -、-NR 6 2. -NR 6 -C(O)-NR 6 2,

[0071] -C(O)-NR 6 2. -C(O)R 6 -C(O)OR 6 -SO2-Ph and -C6F5. R 6 Independently, they are the same or different and are hydrogen atoms or monovalent hydrocarbon groups having 1 to 20 carbon atoms, and Ph is phenyl.

[0072] R 4Examples of groups are alkyl groups, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, tert-pentyl; hexyl, such as n-hexyl; heptyl, such as n-heptyl; octyl, such as n-octyl; and isooctyl, such as 2,2,4-trimethylpentyl; nonyl, such as n-nonyl; decyl, such as n-decyl; dodecyl, such as n-dodecyl; and octadecyl, such as n-octadecyl; cycloalkyl, such as cyclopentyl, cyclohexyl, cycloheptyl, and methylcyclohexyl; aryl, such as phenyl, naphthyl, anthracene, and phenanthryl; alkylaryl, such as o-, m-, and p-tolyl; xylyl and ethylphenyl; and aralkyl, such as benzyl, α-, and β-phenylethyl.

[0073] Replacement R 4 Examples of groups are alkyl halides, such as 3,3,3-trifluoro-n-propyl, 2,2,2,2',2',2'-hexafluoroisopropyl, heptafluoroisopropyl, and aryl halides, such as ortho, meta, and p-chlorophenyl, and -(CH2)-N(R 6 )C(O)NR 6 2. -(CH2) o -C(O)NR 6 2. -(CH2) o -C(O)R 6 -(CH2) o -C(O)OR 6 -(CH2) o -C(O)NR 6 2. -(CH2)-C(O)-(CH2) p C(O)CH3、-(CH2)-O-CO-R 6 -(CH2)-NR 6 -(CH2) p -NR 6 2. -(CH2) o -O-(CH2) p CH(OH)CH2OH, -(CH2) o (OCH2CH2) p OR 6 -(CH2) o -SO2-Ph and -(CH2) o -O-C6F5, where R 6 Ph conforms to the definition given above, and o and p are the same or different integers between 0 and 10.

[0074] R, as a divalent group Si-bonded at either end according to formula (I) 4 The examples are derived from the above for R 4The groups given as monovalent examples contain additional bonds through the substitution of hydrogen atoms; examples of such groups are -(CH2)-, -CH(CH3)-, -C(CH3)2-, -CH(CH3)-CH2-, -C6H4-, -CH(Ph)-CH2-, -C(CF3)2-, and -(CH2). o -C6H4-(CH2) o -、-(CH2) o -C6H4-C6H4-(CH2) o -、-(CH2O) p (CH2CH2O) o -(CH2) o -O x -C6H4-SO2-C6H4-O x -(CH2) o - where x is 0 or 1, and Ph, o, and p have the definitions given above.

[0075] R 4 The group is preferably a monovalent SiC-bonded, optionally substituted hydrocarbon group that does not contain aliphatic carbon-carbon multiple bonds and has 1 to 18 carbon atoms, more preferably a monovalent SiC-bonded hydrocarbon group that does not contain aliphatic carbon-carbon multiple bonds and has 1 to 6 carbon atoms, especially methyl or phenyl.

[0076] R 5 The group can be any group that can undergo addition reactions (hydrosilanization) with SiH functional compounds.

[0077] If R 5 The functional groups include SiC-bonded substituted hydrocarbon groups, with preferred substituents being halogen atoms, cyano groups, and -OR groups. 6 , where R 6 It has the definitions given above.

[0078] R 5 The groups preferably include alkenyl and ynyl groups having 2 to 16 carbon atoms, such as vinyl, allyl, methylallyl, 1-propenyl, 5-hexenyl, ethynyl, butadienyl, hexadienyl, cyclopentenyl, cyclopentadienyl, cyclohexenyl, vinylcyclohexylethyl, divinylcyclohexylethyl, norbornenyl, vinylphenyl, and styryl, with vinyl, allyl, and hexenyl being particularly preferred.

[0079] The molecular weight of component (A) can vary over a wide range, for example, in the range of 10. 2 Up to 10 6Between g / mol. For example, component (A) can be an alkenyl-functionalized oligomeric siloxane with a relatively low molecular weight, such as 1,2-divinyltetramethyldisiloxane, but it can also be a highly polymeric polydimethylsiloxane with Si-bonded vinyl groups at chain or terminal positions, for example, having 10 g / mol. 5 The molecular weight is measured in g / mol (number mean determined by NMR). The molecular structure of component (A) is also not fixed; more specifically, the structure of the macromolecular (i.e., oligomeric or polymeric) siloxane can be linear, cyclic, branched, resinous, or network-like. Linear and cyclic polysiloxanes are preferably of formula R. 4 3SiO 1 / 2 R 5 R 4 2SiO 1 / 2 R 5 R 4 SiO 1 / 2 and R 4 2SiO 2 / 2 The unit composition, where R 4 and R 5 With the definitions given above, branched and network polysiloxanes further contain trifunctional and / or tetrafunctional units, preferably R. 4 SiO 3 / 2 R 5 SiO 3 / 2 and SiO 4 / 2 Those. Of course, a mixture of different siloxanes that meet the standards of component (A) can also be used.

[0080] As component (A), a vinyl-functional, substantially linear polydiorganosiloxane is particularly preferred, having a viscosity of 10 to 100,000 mPa·s, more preferably 15 to 20,000 mPa·s, and especially preferably 20 to 2,000 mPa·s at 25°C in each case.

[0081] As the organosilicon compound (B), any hydrogen-functional organosilicon compound that has been used to date in addition-crosslinkable compositions can be used.

[0082] The organopolysiloxane (B) used, having Si-bonded hydrogen atoms, is preferably a linear, cyclic, or branched organopolysiloxane composed of units of general formula (III).

[0083] R 4 c H d SiO (4-c-d) / 2 (III)

[0084] in

[0085] R 4Based on the definitions given above,

[0086] c is 0, 1, 2, or 3, and

[0087] d is 0, 1, or 2.

[0088] The condition is that the sum of c+d is not greater than 3 and each molecule has at least two Si-bonded hydrogen atoms. Preferably, at least one organopolysiloxane (B) with at least three, more preferably at least four Si-bonded hydrogen atoms per molecule is present.

[0089] The organopolysiloxane (B) used according to the present invention preferably contains Si-bonded hydrogen in the range of 0.01 to 1.7 wt% (by weight), preferably in the range of 0.02 to 0.8 wt%, and more preferably in the range of 0.03 to 0.3 wt% based on the total weight of the organopolysiloxane (B).

[0090] The molecular weight of component (B) can also vary over a wide range, for example, in the range of 10. 2 Up to 10 6 Between g / mol. For example, component (B) can be a relatively low molecular weight SiH-functional oligomeric siloxane, such as tetramethyldisiloxane, but it can also be a highly polymeric polydimethylsiloxane or a silicone resin having SiH groups at the chain or terminal positions.

[0091] The molecular structure of component (B) is not fixed; more specifically, the structure of the macromolecule (i.e., oligomeric or polymeric SiH-containing siloxanes) can be linear, cyclic, branched, resinous, or network-like. Linear and cyclic polysiloxanes (B) are preferably of formula R. 4 3SiO 1 / 2 HR 4 2SiO 1 / 2 HR 4 SiO 2 / 2 and R 4 2SiO 2 / 2 The unit composition, where R 4 With the definitions given above, branched and network polysiloxanes further contain trifunctional and / or tetrafunctional units, preferably R. 4 SiO 3 / 2 HSiO 3 / 2 and SiO 4 / 2 Of those, R 4 It has the definitions given above.

[0092] Of course, mixtures of different siloxanes that meet the criteria of component (B) can also be used. Particularly preferred are low molecular weight SiH-functionalized compounds such as tetra(dimethylsiloxy)silane and tetramethylcyclotetrasiloxane, as well as higher molecular weight SiH-containing siloxanes such as poly(hydromethyl)siloxane and poly(dimethylhydromethyl)siloxane, or similar SiH-containing compounds in which some of the methyl groups have been replaced by 3,3,3-trifluoropropyl or phenyl groups.

[0093] As component (B), particularly preferred are poly(dimethylhydromethyl)siloxanes containing SiH that are substantially linear and have a viscosity in the range of 1 to 100,000 mPa·s, preferably in the range of 2 to 1,000 mPa·s, more preferably in the range of 3 to 750 mPa·s, and especially preferably in the range of 5 to 500 mPa·s, at 25°C in each case.

[0094] Component (B) is preferably present in the crosslinkable silicone composition (S) according to the invention in such an amount that the molar ratio of SiH groups from (A) to aliphatic unsaturated groups is 0.1 to 10, more preferably between 0.5 and 5.0, and especially between 0.5 and 3.

[0095] In a particularly preferred embodiment, the addition-crosslinked silicone composition (S) according to the invention contains

[0096] - At least one, preferably a linear organopolysiloxane (B), having at least three, more preferably at least four Si-bonded hydrogen atoms per molecule, and simultaneously

[0097] - At least one linear polydimethylsiloxane (B) having Me2Si-H end caps at either end,

[0098] Among them, based on the total amount of organopolysiloxane (B), preferably there is at least 50% by weight of linear polydimethylsiloxane (B) having Me2Si-H end caps at either end.

[0099] The components (A) and (B) used in this invention are commercial products or can be prepared by standard chemical methods.

[0100] In addition to components (A) and (B), the silicone composition (S) according to the invention may contain an organopolysiloxane (C) that simultaneously contains aliphatic carbon-carbon multiple bonds and Si-bonded hydrogen atoms. The silicone composition (S) according to the invention may also contain all three components (A), (B), and (C).

[0101] If siloxanes (C) are used, those preferably consist of units of general formulas (IV), (V), and (VI):

[0102] R 4 f SiO 4 / 2 (IV)

[0103] R 4 g R 5 SiO 3-g / 2 (V)

[0104] R 4 h HSiO 3-h / 2 (VI)

[0105] in

[0106] R 4 and R 5 Based on the definitions given above,

[0107] f is 0, 1, 2, or 3.

[0108] g is 0, 1, or 2, and

[0109] h is 0, 1, or 2.

[0110] The condition is that each molecule contains at least 2 Rs. 5 A group and at least two Si-bonded hydrogen atoms.

[0111] Examples of organopolysiloxanes (C) are derived from SO 4 / 2 R 4 3SiO 1 / 2 R 4 3SiO 1 / 2 R 4 2R 5 SiO 1 / 2 and R 4 2HSiO 1 / 2 Those composed of units (referred to as MP resins), wherein these resins may additionally contain R 4 SiO 3 / 2 and R 4 2SiO unit, and basically composed of R 4 2R 5 SiO 1 / 2 R 4 2SiO and R 4 HSiO unit (where R) 4 and R 5 Straight-chain organopolysiloxanes (as defined above) are composed of linear organopolysiloxanes.

[0112] In each case, at 25°C, the organopolysiloxane (C) preferably has an average viscosity of 0.01 to 500,000 Pa·s, more preferably 0.1 to 100,000 Pa·s. The organopolysiloxane (C) can be prepared by standard chemical methods.

[0113] As the hydrosilylation catalyst (D), any thermosetting or UV-curing catalyst known from the prior art can be used. Component (D) can be a molybdenum group metal, such as molybdenum, rhodium, ruthenium, palladium, osmium, or iridium, an organometallic compound, or a combination thereof. Examples of component (D) are compounds such as hexachloromolybdic acid (IV), molybdenum dichloride, molybdenum acetylacetonate, and complexes of said compounds encapsulated in a matrix or core / shell structure. Platinum complexes of organopolysiloxanes with low molecular weight include 1,3-divinyl-1,1,3,3-tetramethyldisiloxane complexes with platinum. Other examples are platinum-phosphite complexes or platinum-phosphine complexes. For light- or UV-curable compositions, it is possible, for example, to use alkyl-platinum complexes, such as derivatives of cyclopentadienyltrimethylplatinum (IV), cyclooctadienyldimethylplatinum (11), or sodium diketone complexes, such as diacetylacetonate platinum (11), to initiate an addition reaction with the aid of light. These compounds can be encapsulated in a resin matrix.

[0114] The concentration of component (D) is sufficient to catalyze the hydrosilylation reaction of components (A), (B), and (C) upon contact, in order to generate the heat required in the described method. Depending on the total weight of the components, the amount of component (D) can be between 0.1 and 1000 ppm, 0.5 and 100 ppm, or 1 and 25 ppm of platinum group metals. When the platinum group metal content is below 1 ppm, the curing rate can be low. Using more than 100 ppm of platinum group metals is uneconomical or reduces the storage stability of the silicone composition.

[0115] The addition-crosslinkable silicone composition (S) may optionally contain all other additives that have been used to date in the production of addition-crosslinkable compositions. An example of an active reinforcing filler (E) not covered by the definition of a thermally conductive filler (Z) that can be used as a component in the addition-crosslinkable silicone composition (Y) according to the invention is one having a molecular weight of at least 50 μm. 2 Fumed or precipitated silica with a BET surface area of ​​ / g, as well as carbon black and activated carbon such as furnace black and acetylene black, preferably having a surface area of ​​at least 50m². 2 / g of BET surface area of ​​fumed and precipitated silica.

[0116] The silica filler (E) mentioned may have hydrophilic properties or may have been hydrophobized by known methods. As a result of surface treatment, the preferred filler (E) has a carbon content of at least 0.01% to a maximum of 20% by weight, preferably between 0.1% and 10% by weight, and more preferably between 0.5% and 6% by weight.

[0117] In the addition-crosslinkable silicone composition (S) according to the invention, component (E) is preferably used in the form of a single subdivided filler or, equally preferably, in a mixture of two or more thereof. In the crosslinkable silicone composition (S) according to the invention, the content of the active reinforcing filler is in the range of 0% to 50% by weight, preferably 0% to 30% by weight, and more preferably 0% to 10% by weight.

[0118] The crosslinkable addition-crosslinkable silicone composition (S) is more preferably characterized in that the filler (E) has been surface-treated. The surface treatment is achieved by methods known in the art for hydrophobic fine fillers.

[0119] The addition-crosslinked silicone composition (S) according to the invention may contain alkyltrialkoxysilanes (F) as an additional additive to reduce its viscosity. If present, they are preferably present in an amount of 0.1-8 wt%, preferably 0.2-6 wt%, based on the total mass of the silicone composition (S), wherein the alkyl group may be a saturated or unsaturated, straight-chain or branched alkyl group having 2 to 20, preferably 8 to 18 carbon atoms, and these alkoxy groups may have 1 to 5 carbon atoms. Examples of alkoxy groups include methoxy, ethoxy, propoxy, and butoxy, with methoxy and ethoxy being particularly preferred. For (F), n-octyltrimethoxysilane, n-dodecyltrimethoxysilane, n-hexadecyltrimethoxysilane, and n-octadecyltrimethoxysilane are particularly preferred.

[0120] In each case, based on the addition-crosslinked silicone composition (S) according to the invention, the addition-crosslinked silicone composition (S) according to the invention may optionally contain up to 70% by weight, preferably up to 42% by weight, as components, which are different from the thermally conductive filler (Z) and additives (E) and (F) according to the invention. For example, these additives may be inactive fillers, resinous polyorganosiloxanes other than siloxanes (A), (B) and (C), non-reinforcing fillers, fungicides, fragrances, rheology modifiers, corrosion inhibitors, oxidation inhibitors, light stabilizers, flame retardants and compositions affecting electrical properties, dispersants, solvents, adhesion promoters, pigments, dyes, plasticizers, organic polymers, heat stabilizers, etc.

[0121] Thermally conductive filler (Z)

[0122] The crosslinkable thermally conductive silicone composition (Y) according to the present invention contains at least one thermally conductive filler (Z) having a thermal conductivity of at least 5 W / mK, provided that the crosslinkable thermally conductive silicone composition (Y) contains at least 20% by volume of metallic silicon particles as thermally conductive filler (Z), which must still satisfy at least other specific characteristics a) to d), and the total amount of thermally conductive filler (Z) is at least 50% by volume.

[0123] a) According to the invention, the average diameter x50 of these metallic silicon particles (Z) is in the range of 30-150 μm, preferably in the range of 30-140 μm, more preferably in the range of 40-130 μm, particularly preferably in the range of 50-125 μm, and especially in the range of 60-120 μm.

[0124] b) The silicon metal particles (Z) according to the invention are primarily spherical and preferably produced by a melting method. The predominantly spherical shape of the particles according to the invention is characterized by a width-to-length ratio (aspect ratio w / l) of at least 0.76, preferably at least 0.77, more preferably at least 0.78, and especially at least 0.79.

[0125] The silicon particles (Z) according to the invention preferably have a sphericity value SPHT of at least 0.75, more preferably at least 0.76, more preferably at least 0.78, and especially preferably at least 0.79.

[0126] In a particularly preferred embodiment, the silicon particles (Z) according to the invention have an aspect ratio of at least 0.76 and simultaneously have a sphericity value SPHT of at least 0.75, preferably at least 0.76, more preferably at least 0.78, and especially preferably at least 0.79.

[0127] c) The particle size distribution range (SPAN) is defined as SPAN = (x90 - x10) / x50. The SPAN of the metallic silicon particles (Z) according to the invention is at least 0.4, preferably at least 0.5, more preferably at least 0.6, and particularly preferably at least 0.7. In a preferred embodiment, the SPAN is between 0.7 and 2.5, particularly between 0.75 and 2.

[0128] Here, it is not important whether a single portion of silicon particles (Z) having a SPAN within the scope of the invention is used, or whether two or more portions of silicon particles are mixed and thus the characteristic c) of the particle size distribution range of the invention of silicon particles (Z) is achieved. If two or more portions of silicon particles are mixed, this can be done before mixing with one or more components of the composition according to the invention, or these portions of silicon particles can be mixed with one or more components of the composition according to the invention separately from each other. The order of addition is irrelevant here.

[0129] Preferably, no more than four parts of silicon particles are mixed to achieve the distribution range according to the invention; more preferably, no more than three parts of silicon particles are mixed to achieve the distribution range according to the invention; more preferably, no more than two parts of silicon particles according to the invention are used to achieve the distribution range according to the invention; and particularly preferably, only a single silicon powder according to the invention is used.

[0130] d) In each case, based on the total amount of silicon particles, the silicon particles (Z) of the present invention contain up to 1.5% by weight of silicon particles smaller than 2 μm, preferably up to 1% by weight, more preferably up to 0.5% by weight. Particularly preferred silicon particles are substantially free of particle portions smaller than 2 μm.

[0131] In each case, based on the total amount of silicon particles, the silicon particles (Z) according to the invention preferably contain less than 20% by weight, more preferably less than 15% by weight, and more preferably less than 10% by weight of a particle portion having a diameter of less than or equal to 20 μm.

[0132] In each case, based on the total amount of silicon particles, the silicon particles (Z) according to the invention preferably contain less than 15% by weight, more preferably less than 10% by weight, and more preferably less than 5% by weight of a particle portion having a diameter of less than or equal to 10 μm.

[0133] In a particularly preferred embodiment, no silicon particles with an average diameter of less than or equal to 10 μm are intended to be added. Preferably, no silicon particles with an average diameter of less than or equal to 15 μm are added. Particularly preferably, no silicon particles with an average diameter of less than or equal to 20 μm are intended to be added.

[0134] Using silicon particles smaller than 20 μm is disadvantageous because such small particles have a relatively low minimum ignition energy and therefore pose a dust explosion hazard, requiring complex and expensive safety precautions in industrial processing. Furthermore, interstitial fillers containing such fine aluminum particles do not meet the flammability requirements according to UL94 V-0. Another disadvantage of very fine or ground silicon particles is that these particles have a relatively high surface area and bind a very large amount of polymer. This significantly increases the viscosity of the silicone composition. Only mixtures with relatively low filler levels and therefore low thermal conductivity can be produced. At higher filler levels, the composition becomes very rigid and can no longer be processed by conventional methods (e.g., dispensers). Silicone compositions containing ground silicon particles have also been found to have relatively high flammability.

[0135] Metallic silicon possesses several highly advantageous properties for use as a thermally conductive filler (Z). For example, the exceptionally high thermal conductivity of silicon particles (Z) improves the thermal conductivity of the thermally conductive silicone composition (Y) produced from them. The low density of these silicon particles (Z) reduces the weight of the composition and the components produced from it, contributing to cost savings. The low electrical conductivity enables the production of electrically insulating components and improves breakdown resistance. The low Mohs hardness of the silicon particles (Z) reduces wear during processing. It will be apparent to those skilled in the art that, as silicon purity decreases, all or part of the aforementioned advantages are lost. The purity of the silicon particles (Z) according to the invention, and therefore the silicon content, is at least 80%, preferably at least 90%, more preferably at least 95%.

[0136] It will also be apparent to those skilled in the art that metallic silicon particles are flammable under certain conditions, and that the dust poses an explosion risk. Those skilled in the art also know that as particle size decreases, the risks of dust formation, flammability, and explosion associated with metal powders increase significantly. For this reason, very small silicon particles smaller than 30 μm are unsuitable for many applications, such as as interstitial fillers in lithium-ion batteries. Due to their low minimum ignition energy, such particles are hazardous to handle and require complex and costly safety precautions in industrial processing. It has also been found that compositions containing very small silicon particles smaller than 30 μm are relatively highly flammable and do not meet the UL94 V-0 flammability rating for interstitial fillers in lithium-ion batteries.

[0137] Larger silicon particles with an average particle size exceeding 30 μm have relatively high minimum ignition energy and are therefore safer and easier to process in industrial processes. However, compositions containing non-inventory milled angular silicon particles larger than 30 μm have been found to be highly flammable and do not meet the UL94 V-0 flammability category for interstitial fillers in lithium-ion batteries.

[0138] Silicon particles with an average particle size exceeding 150 μm are unsuitable for many thermally conductive silicone compositions because such large particles are often unsuitable for fine gaps that must be filled, for example, with interstitial fillers. Furthermore, such large-grained silicon particles have been found to exhibit relatively high flammability.

[0139] The use of spherical fillers to improve the flowability and processability of filled polymers is well known in the art. However, only a few prior art documents exist in which spherical silicon particles are used in thermally conductive silicone compositions. The disclosed compositions contain only very small spherical silicon particles with an average particle size of less than 25 μm, and their disadvantages have been described.

[0140] It has been found, quite unexpectedly, that the crosslinkable silicone compositions (Y) according to the invention are thermally conductive and, when they contain metallic silicon particles according to the invention that simultaneously satisfy the required minimum amounts of features a) to d), are also low in flammability.

[0141] The crosslinkable silicone composition (Y) according to the invention contains at least 20% by weight of such metallic silicon particles (Z), preferably at least 25% by volume, more preferably at least 30% by volume, and especially preferably at least 35% by volume. If the silicone composition (Y) contains a smaller amount of metallic silicon particles (Z), the desired beneficial effects of metallic silicon, such as low density and high thermal conductivity, are no longer sufficiently provided.

[0142] Prior art includes various methods for producing finely shaped metallic particles with a spherical shape. The silicon particles (Z) according to the invention are preferably produced in a molten state, resulting in relatively smooth surfaces and substantially free of cracks, sharp edges, and pointed corners. In this way, they differ from conventional abrasive particles that have already been transformed into their final form, for example, by crushing, grinding, or polishing. Here, it is not important whether these particles are cold-crushed (e.g., by grinding) in a first process step and then transformed into a molten form by heating above their melting point (e.g., by heat treatment in a hot zone, such as by plasma), or whether a silicon melt is first produced and then crushed (e.g., by atomization). The silicon particles according to the invention are preferably transformed into the solid form according to the invention by spraying or atomizing a silicon melt, followed by cooling.

[0143] Suitable methods for producing silicon particles (Z) according to the invention are known to those skilled in the art and are described, for example, in Chapter 2.2 of “Pulvermetallurgy: Technologien and Werkstoffe [Powder Metallurgy: Technologies and Materials], Schatt, Werner, Wieters, Klaus-Peter, Kieback, Bernd, pp. 5-48, ISBN 978-3-540-681112-0, E-Book: https: / / doi.org / 10.1007 / 978-3-540-68112-0_2”. A preferred method for producing silicon particles (Z) according to the invention is inert gas atomization, also known as gas atomization, pressurized water atomization, also known as liquid atomization or water atomization, or melt spinning, also known as centrifugal atomization or rotary atomization.

[0144] The described method allows for the production of metallic silicon particles in very different particle size ranges, particularly in the range of average particle size from a few micrometers to a few millimeters. It is also possible to produce these metallic silicon particles in very different particle forms, such as “splashed,” i.e., very irregular, elliptical, or spherical, and with a very variable particle size distribution. Quite unexpectedly, the advantageous properties according to the invention, especially the relatively low flammability, have been found to be exhibited only by those silicon particles that are primarily spherical and simultaneously achieve features a) to d) of the invention.

[0145] The method for producing the metallic silicon particles (Z) according to the invention should preferably be carried out in such a manner that the particles are obtained in their predominantly spherical form according to the invention and thus satisfy characteristics a)-d) and are substantially free of splashed, nodular, angular, or sharp particles. These solidified particles can be separated by size in subsequent process steps using standard methods, such as by sieving or screening. In these methods, agglomerates and bonded particles can be separated, but substantially no particles are destroyed. "Predominantly spherical" and "substantially free" mean that the presence of these particles is within the range of "impurities" in the particles (Z) according to the invention and is permissible and does not detract from their inventive effects.

[0146] In addition to these metallic silicon particles (Z), the crosslinkable silicone composition (Y) according to the invention may contain an additional thermally conductive filler (Z) having a thermal conductivity greater than 5 W / mK. Examples of such additional thermally conductive fillers (Z) are magnesium oxide, aluminum powder, silver powder, zinc oxide, boron nitride, silicon carbide, aluminum nitride, aluminum hydroxide, aluminum oxide, graphite, etc. Preferred additional fillers are aluminum powder, magnesium oxide, aluminum hydroxide, zinc oxide, and aluminum oxide. Particularly preferred fillers are aluminum hydroxide and aluminum oxide, with aluminum hydroxide being particularly preferred. The shape of the additional filler is substantially unrestricted. The particles may be, for example, spherical, elliptical, needle-like, tubular, sheet-like, fibrous, or irregular in shape. They preferably have a spherical, ellipsoidal, or irregular shape. The average diameter of the additional thermally conductive filler (Z) is preferably in the range of 0.01-150 μm, more preferably in the range of 0.1-100 μm, more preferably in the range of 0.2-80 μm, and particularly in the range of 0.4-60 μm.

[0147] Highly dense fillers are disadvantageous in use, for example in aircraft and electric vehicles, because they significantly increase the weight of components. Additional thermally conductive fillers (Z) preferably have a density of no more than 6.0 g / cm³. 3 Preferably, the concentration is no greater than 4.5 g / cm³. 3 More preferably, not more than 3.0 g / cm³ 3 The density.

[0148] In many applications, electrical conductivity of the thermally conductive composition is undesirable because it can lead to, for example, short circuits. The composition (Y) according to the invention preferably contains only components having a conductivity of at least 1 Ω·mm². 2 Thermally conductive filler with a resistivity of / m (Z).

[0149] The preferred crosslinkable silicone composition (Y) according to the invention comprises metallic silicon particles according to the invention as the sole thermally conductive filler (Z) or in combination with up to two other thermally conductive fillers (Z). Here, up to 5% of impurities are not considered as additional fillers (Z).

[0150] If the preferred composition according to the invention comprises metallic silicon particles (Z) according to the invention as the sole thermally conductive filler (Z) having a thermal conductivity greater than 5 W / mK, then a rheology modifier or thickener to prevent filler sedimentation is preferably added. Suitable rheology modifiers are known to those skilled in the art, preferably fumed silica, such as component (E).

[0151] The total amount of thermally conductive filler (Z) in the crosslinkable thermally conductive silicone composition (Y) according to the invention is 50%-95% by volume, preferably 60%-90% by volume, and more preferably 65%-88% by volume. If the silicone composition (Y) contains a small amount of thermally conductive filler (Z), the thermal conductivity will be insufficient; if the silicone composition (Y) contains a large amount of thermally conductive filler (Z), then the composition (Y) will be difficult to process because it will have high viscosity or even brittleness.

[0152] The uncrosslinked thermally conductive silicone composition (Y) according to the invention has a thermal conductivity of at least 0.6 W / mK, preferably at least 0.8 W / mK, more preferably at least 1.2 W / mK, and especially at least 1.5 W / mK.

[0153] The viscosity of the uncrosslinked thermally conductive silicone composition (Y) according to the invention can vary over a very wide range and be matched to the requirements of the application. The viscosity of the uncrosslinked thermally conductive silicone composition (Y) according to the invention is preferably adjusted by standard methods from the prior art via the content of the thermally conductive filler (Z) and / or the composition of the silicone composition (S). These are known to those skilled in the art. The viscosity is preferably adjusted by selecting and combining components (A), (B), and (C) and optionally adding rheology modifiers and / or active fillers (E) and / or alkyltrialkoxysilanes (F).

[0154] The dynamic viscosity of the uncrosslinked, thermally conductive silicone composition (Y) according to the invention is preferably in the range of 100-1,000,000 mPa·s, more preferably in the range of 1,000-750,000 mPa·s, more preferably in the range of 2,000-500,000 mPa·s, and especially not greater than 250,000 mPa·s, in each case at a shear rate D = 10 s. -1 At 25℃.

[0155] The density of the uncrosslinked silicone composition (Y) according to the present invention is less than 3.5 g / cm³. 3 Preferably less than 3.0 g / cm³ 3 More preferably less than 2.5 g / cm³ 3 Especially less than 2.3g / cm 3 .

[0156] The present invention further provides a method for producing a crosslinkable silicone composition (Y) according to the invention by mixing individual components.

[0157] These components can be mixed using conventional continuous and batch methods of existing technology. Suitable mixing equipment is any known apparatus. Examples of these are single-shaft or bi-shaft continuous mixers, twin-roll mixers, Ross mixers, Hobart mixers, dental mixers, planetary mixers, kneaders, and Henschel mixers or similar mixers. Mixing is preferably carried out in a planetary mixer, kneader, or continuous mixer. The crosslinkable silicone composition (Y) can optionally be heated during mixing, preferably in a temperature range of 15-40°C. Procedures for producing the preferred addition-crosslinkable silicone composition (S) are also known to those skilled in the art. In principle, components can be added in any order. For example, components e) and optionally g) can be premixed and then mixed with components a) and / or b). It is also optional to heat the mixture here. It is preferred to mix at least a portion of a) and alkoxysilane g) and then mix in a thermally conductive filler (Z). Production is preferably carried out without active heating.

[0158] The crosslinkable silicone composition (Y) according to the invention can be provided as a one-component, two-component, or multi-component mixture. Examples are two-component thermocurable compositions (Y) or one-component UV-curable compositions (Y). This is also well known to those skilled in the art.

[0159] The crosslinkable silicone composition (Y) according to the present invention has very good processing properties with respect to flowability, gap filling performance and layer thickness control, and can be applied precisely.

[0160] The temperature conditions for curing the silicone composition (Y) that is preferably curable by a hydrogen silanization reaction are not limited, and are generally in the range of 20°C to 180°C, preferably in the range of 20°C to 150°C, and even more preferably in the range of 20°C to 80°C.

[0161] The present invention further provides silicone products obtained by dispensing or applying and then crosslinking / curing a crosslinkable silicone composition. The cured silicone products (e.g., thermally conductive elements) exhibit excellent thermal conductivity and precise layer thickness.

[0162] The hardness of the crosslinked thermally conductive silicone composition (Y) according to the invention can vary over a very wide range and be matched to the requirements of the application. For example, for applications as gap fillers, a softer and more flexible product is preferred; however, for applications as thermally conductive adhesives, a harder and more robust product is preferred. The hardness of the crosslinked thermally conductive silicone composition (Y) according to the invention is preferably adjusted via a composition of the silicone composition (S) using standard methods from the prior art. These are known to those skilled in the art. Preferably, the hardness is adjusted by selecting and combining components (A), (B), and (C) and optionally adding a reinforcing filler (E).

[0163] The hardness of the cured silicone product is preferably in the range of 2 to 100 on the Shore 00 scale, and more preferably in the range of 10 to 85 on the Shore 00 scale. For applications as interstitial fillers, the hardness of the crosslinked thermally conductive silicone composition according to the invention is particularly preferably in the range of 15 to 65 on the Shore 00 scale.

[0164] The cross-linked silicone product has a thermal conductivity of at least 0.6 W / mK, preferably at least 0.8 W / mK, more preferably at least 1.2 W / mK, and especially at least 1.5 W / mK.

[0165] The present invention further provides the use of crosslinkable silicone compositions as gap fillers (i.e., thermally conductive elements), thermally conductive pads, thermally conductive adhesives, and encapsulation compounds. They are particularly suitable for use as gap fillers in lithium-ion batteries for electric vehicles.

[0166] The density of the cross-linked silicone product according to the present invention is less than 3.5 g / cm³. 3 Preferably less than 3.0 g / cm³ 3 More preferably less than 2.5 g / cm³ 3 Especially less than 2.3g / cm 3 .

[0167] The cross-linked silicone products according to the present invention preferably conform to the UL94 V-0 flammability category.

[0168] In a preferred embodiment, the density of the cross-linked silicone product according to the present invention is less than 2.5 g / cm³. 3 Furthermore, the thermal conductivity is greater than 1.8 W / mK, and the flammability meets UL94 V-0, provided that the dynamic viscosity of the uncrosslinked silicone composition according to the invention is less than 500,000 mPa·s, particularly less than 250,000 mPa·s, in each case at a shear rate D = 10 s⁻¹. -1 At 25℃.

[0169] In a particularly preferred embodiment, the density of the silicone product according to the present invention is less than 2.3 g / cm³. 3 Furthermore, the thermal conductivity is greater than 1.8 W / mK, preferably greater than 3.0 W / mK, and the flammability meets UL94 V-0, provided that the dynamic viscosity of the uncrosslinked silicone composition according to the invention is less than 500,000 mPa·s, particularly less than 250,000 mPa·s, in each case at a shear rate D = 10 s⁻¹. -1 At 25℃.

[0170] Test methods

[0171] Measurement of thermal conductivity λ

[0172] Thermal conductivity was measured using a TIM (Steinbeis Transfer Zentrum) instrument. Management inder Elektronik, Lindenstr) was determined according to ASTM D5470-12. 13 / 1, 72141 (Germany). This method uses a constant heat flow to determine the thermal resistance of the sample between two test cylinders. The layer thickness of the sample is used to calculate the effective thermal conductivity.

[0173] For measurement, the sample was applied using a template, and the graduated cylinder was manually narrowed to a thickness of 1.9–2.0 mm, after which excess material was removed. Thermal conductivity was measured at a constant gap of 1.8–1.6–1.4–1.2–1.0 mm. Evaluation was performed using integrated report locations. After a plausibility test (linearity determination coefficient > 0.998), the thermal conductivity λ was reported as the effective thermal conductivity in W / (m*K).

[0174] Measurement of dynamic viscosity

[0175] Dynamic viscosity was measured using an Anton Paar MCR 302 rheometer with flow profiles having the following parameters, according to DIN EN ISO 3219:1994 and DIN 53019: Measurement type: T / D; Temperature: 25.0℃; Measuring element: PP25; Measuring gap: 0.50 mm; Shear rate: 0.1-10 s. -1 Time: 120 seconds; Measurement: 30. Viscosity reported in Pa·s at a shear rate D = 10 s. -1 Interpolated values ​​under the given conditions.

[0176] Density measurement

[0177] The density of the uncrosslinked thermally conductive silicone composition is determined according to ISO 1183, and the density of the crosslinked thermally conductive silicone composition is determined according to ISO 1184.

[0178] Particle size and particle shape analysis

[0179] Particle size (mean diameter x 50), particle size distribution (parameters: standard deviation σ and distribution range SPAN), and particle shape (parameters: aspect ratio w / l and sphericity SPHT) were analyzed using a Retsch Technology Camsizer X2 (measurement principle: dynamic image analysis), conforming to ISO 13322-2 and ISO 9276-6 (analytical method: dry measurement of powders and particles; measurement range: 0.8 μm-30 mm; compressed air dispersion using "X-Jet"; dispersion pressure = 0.3 bar). Evaluation was volume-based and performed using X... c min The model is analyzed.

[0180] The following embodiments illustrate the basic implementability of the invention, but are not limited to what is disclosed therein.

[0181] In the following examples, all figures for parts and percentages are based on weight unless otherwise stated. Unless otherwise stated, the following examples were conducted at ambient atmospheric pressure, i.e., at approximately 1000 hPa, and at room temperature, i.e., approximately 20°C, or at room temperature without additional heating or cooling of the reactant combination. Example

[0182] Overview of silicon powders and silicon powder mixtures used in this invention and in non-inventive forms.

[0183] Table 1 summarizes the characteristics of the silicon powders of the present invention and those not of the present invention used in the examples.

[0184] Examples 1-6 of the present invention use silicon powders of the present invention, which have been obtained by atomization with an inert gas and are therefore primarily spherical, and additionally have a relatively wide particle size distribution according to the present invention.

[0185] Comparative embodiments V1-V4 (non-inventive) use non-inventive silicon powders that have been obtained by atomization with an inert gas and are therefore primarily spherical, but have a relatively narrow, non-inventive particle size distribution and do not satisfy feature c of the invention.

[0186] Comparative embodiment V8 (not an invention) uses a silicon powder that is not of this invention. This silicon powder has been obtained by atomization with an inert gas, but has a very irregular nodular form and does not satisfy feature b of the invention.

[0187] Comparative embodiments V5-V7 (non-inventive) use silicon powder that is not of the present invention. This non-inventive silicon powder has a relatively wide particle size distribution, but has been obtained by a grinding method and therefore has essentially sharp edges and does not satisfy feature b) of the invention. Comparative embodiment V7 has 3.8% by weight of silicon particles smaller than 2 μm and therefore also does not satisfy feature d).

[0188] Example 7: Production of silicon powder mixture 7 (this invention)

[0189] 100g of non-inventive silicon powder from Comparative Example V2, 200g of non-inventive silicon powder from Comparative Example V3, 400g of non-inventive silicon powder having a x50 of 105.4μm, a SPAN of 0.35, a w / l of 0.83, and a SPHT of 0.92, 200g of non-inventive silicon powder having a x50 of 133.8μm, a SPAN of 0.25, a w / l of 0.82, and a SPHT of 0.94, and 100g of non-inventive silicon powder from Comparative Example V4 were mixed in a commercial RW 28 laboratory stirrer system. The silicon powder mixture of the present invention was uniformly mixed in (Werke GmbH & Co. KG, 79219 Staufen, Germany). The resulting mixture had a x50 of 107.8 μm, a SPAN of 0.75, a w / l of 0.83, and a SPHT of 0.91, and satisfied the features a)-d) of the invention.

[0190] Comparative Example V9: Production of Silicon Powder Mixture V9 (not of this invention)

[0191] 300 g of non-inventive silicon powder having a x50 of 133.8 μm, a SPAN of 0.25, a w / l of 0.82, and a SPHT of 0.94, and 600 g of non-inventive silicon powder from Comparative Example V4 were mixed in a commercial RW 28 laboratory stirrer system. -Werke GmbH & Co. KG, 79219 Staufen, Germany) uniformly mixed. The resulting silicon powder mixture is not of the present invention, having a x50 of 155.1 μm, a SPAN of 0.41, a w / l of 0.82, and a SPHT of 0.94, and does not satisfy characteristic a) of the present invention.

[0192] abbreviation

[0193] Example

[0194] V Comparative Example

[0195] PS particle shape

[0196] r is mainly circular, e has angles, n is nodule, I is the NI of this invention, not the nd of this invention, and nd is undetermined.

[0197] Table 1: Overview of the silicon powder used

[0198]

[0199]

[0200] *Within the measurement accuracy range, the content of silicon particles <2μm is 0.0% by weight. **The content of silicon particles <2μm is 3.8% by weight.

[0201] General Method 1 (GM1) for Producing Silicone Molded Articles of Crosslinked Thermally Conductive Silicon-Containing Powder (Examples 8 to 14 of the Invention and Examples V10 to V22 of Non-Invention)

[0202] Step 1: Preparation of an addition-crosslinkable, thermally conductive silicone composition containing silicon powder

[0203] 24.5 g of vinyl dimethylsiloxy-terminated polydimethylsiloxane with a viscosity of 1000 mPa·s, 16.3 g of hydrogenated dimethylsiloxy-terminated polydimethylsiloxane with a viscosity of 1000 mPa·s, and 1.0 g of a copolymer composed of dimethylsiloxy, methylhydrosiloxy, and trimethylsiloxy units with a viscosity of 200 mPa·s and a Si-bonded hydrogen content of 0.18 wt%.

[0204] Homogenize for 25 seconds at 2350 rpm using a SpeedMixer DAC 400FVZ (Hauschild & Co KG, Waterkamp 1, 59075 Hamm, Germany). Afterward, in each case, silicon powder is added at the ratios shown in Table 2 and mixed for 25 seconds using a SpeedMixer. The silicone composition containing silicon particles is stirred with a spatula to mix any remaining silicon powder from the container edge. Homogenize again for 25 seconds using a SpeedMixer and cool to room temperature.

[0205] For cross-linking, add 4.18g. CAT PT (available from Wacker Chemie AG, Hanns-Seidel-Platz 4, 81737 Munich, Germany) corresponds to a mixing ratio of 1 part catalyst solution to 10 parts silicone composition, excluding the proportion of thermally conductive filler (Z). The mixture was mixed three times at 2350 rpm using a SpeedMixer for 10 seconds each time, with the sample stirred by a spatula between mixing operations. The result is a reactive paste that can only be stored for a few hours and requires further direct processing.

[0206] Step 2: Preparation of cross-linked, thermally conductive silicone-containing powder silicone molded body

[0207] Using standard existing technical methods, at 165℃ and 380 N / cm 2 A molded body with dimensions of 207mm x 207mm x 2mm is produced by compression vulcanization in a stainless steel mold for 5 minutes. The cured rubber is then heat-treated at 200°C for 4 hours. The resulting molded body is uniform and elastic.

[0208] Example 15 Flammability Test

[0209] Flammability is tested in a simplified test based on UL 94V (a standard from Underwriters Laboratories for vertical burning tests), which allows plastics to be classified by their flame retardancy. This method is the most common test used for classifying flame-retardant plastics.

[0210] Test pieces with a length of 5” (127 mm) and a width of 0.5” (12.7 mm) were stamped from the silicone molded bodies of the present invention according to Examples 8 to 14 and the non-inventive silicone molded bodies according to Comparative Examples V10 to V14 and V19 to V22. The plate was fixed vertically at its upper end at a length of 1 / 4”. A piece of absorbent cotton was placed 12” (305 mm) below the test plate. The burner was adjusted to form a blue flame with a length of 3 / 4”. The flame was guided from a distance of 3 / 8” (9.5 mm) to the lower edge of the plastic plate. After 10 seconds of contact, the flame was removed. The afterflame time (total afterflame time and afterglow time) of the sample was recorded. The sample should extinguish immediately after flame removal and burn for no more than another 4 seconds. Tests were conducted on 5 different samples, and the average afterflame time was determined. The results can be found in Table 2.

[0211] In the non-inventive comparative experiments V15 to V18, each contained 62.5 vol% of non-inventive silicon particles according to comparative examples V5 to V8, which more specifically did not satisfy feature b), forming a very high viscosity silicone composition that could not be pressed to produce a suitable silicone molded body.

[0212] Table 2: Composition and flammability of silicone compositions containing silicone powder

[0213]

[0214]

[0215] In flammability testing, comparative examples V10 to V14 and V19 to V22, which contained non-inventive silicon powder or mixtures of non-inventive silicon powder (not satisfying characteristics a) to d) according to comparative examples V1-V9, exhibited relatively high flammability. Particularly noteworthy are the flammability of the non-inventive comparative sample V21 (containing silicon powder with an average particle size of less than 20 μm) and the flammability of the non-inventive comparative sample V22 (containing silicon powder with a very irregular nodular particle shape). After flame removal, both samples continued to burn until the molded body was completely burned.

[0216] Completely unexpectedly, it was found that silicon powders simultaneously satisfying characteristics a)-d) exhibited the advantage of reduced flammability according to the present invention. Furthermore, in Example 14 of the present invention, it was completely unexpectedly found that mixing various non-inventive silicon powders could produce a silicon powder mixture according to the present invention with the advantageous property of low flammability, provided that the resulting mixture satisfied characteristics a) to d). In contrast, the non-inventive silicon powder mixture from Comparative Example V8 did not satisfy characteristics a) to d) and did not demonstrate any advantage according to the present invention.

[0217] Example 16 Complete flammability test according to UL 94V

[0218] The silicone molded articles of the present invention from Embodiments 11 and 12, and the non-inventive silicone molded articles from Comparative Embodiments V11, V12, and V20, were subjected to a complete flammability test according to UL 94V and classified as V-0, V-1, or V-2. For many industrial applications, especially for use as gap fillers in electric vehicles, a V-0 rating is required. The results can be found in Table 3.

[0219] Table 3: Flammability test according to UL 94V

[0220] 11 V-0 I 12 V-0 I V11 V-1 NI V12 V-1 NI V20 V-2 NI

[0221] Example 17 Preparation of a cross-linked thermally conductive silicone molded body containing an in-situ mixture of two types of silicon powder (the present invention).

[0222] According to general method GM1, the crosslinkable thermally conductive silicone composition of the present invention was produced by using 164.90 g of the silicon powder of the present invention from Example 1 (37.6 vol% of the total amount of the thermally conductive silicone composition) and 161.74 g of non-inventory silicon powder having a size of 105.4 μm x 50 as silicon powder, with SPAN of 0.35, w / l of 0.83 and SPHT of 0.92 (36.8 vol%, based on the total weight of the thermally conductive silicone composition), and these were mixed in situ to form the silicon powder mixture of the present invention.

[0223] The obtained product has a silicon particle content of 74.4% by volume of the present invention and a shear rate of D = 10 s⁻¹. -1 The reactive silicone composition of the present invention has a dynamic viscosity of 64,800 mPa·s at 25°C. It has a thermal conductivity of 4.98 W / mK and a density of 1.97 g / cm³. 3 The pellets according to the invention exhibit good processability, high thermal conductivity, and low density, and are highly suitable for use as interstitial fillers. General method GM1 is used to produce the crosslinked silicone molded articles of the invention. The afterflame time according to Example 15 is 1.3 seconds. Example 16 produces a UL94 V-0 classification.

[0224] Comparative Example V23 describes the production of a cross-linked silicone molded article comprising an in-situ mixture of two types of silicon powder (not of this invention).

[0225] Crosslinked silicone molded articles were prepared according to Example 17 of the present invention, except that 19.0 vol% of the silicon powder of Example 1 and 18.6 vol% of the silicon powder with X50 of 105.4 μm, SPAN of 0.35, w / l of 0.83 and SPHT of 0.92 were used.

[0226] The non-inventive silicone molded article has a total content of 37.6% by volume of the non-inventive thermally conductive filler (Z) and a thermal conductivity of 0.5 W / mK. Example 16 yields a UL94 V-1 classification. This composition is not suitable for use as a gap filler.

[0227] Example 18 Two-component interstitial packing (this invention)

[0228] Production of Component A

[0229] In a commercial Labopto planetary mixer (PC Laborsystem GmbH, Maiswischerstrasse 6, 4312 Magden, Switzerland) equipped with two rod agitators and a stripper, 115.4 g of vinyl dimethylsiloxy-terminated polydimethylsiloxane with a viscosity of 120 mPa·s and 1.1 g of... CATALYST EP (available from Wacker Chemie AG, Hanns-Seidel-Platz 4, 81737 Munich, Germany) is mixed for 5 minutes at room temperature and 300 rpm. Then, 308.5 g of DAW-05 spherical alumina (available from Denka Company Limited, Nihonbashi Mitsui Tower, 1-1, Nihonbashi-Muromachi 2-chome, Chuo-ku, Tokyo 103-8338, JAPAN) is added and mixed evenly at 300 rpm for 10 minutes under slight reduced pressure (950 mbar). Subsequently, a total of 578.8 g of the silicon powder of the present invention was added in two portions (part 1: 385.9 g, part 2: 192.9 g), the silicon powder having an X50 of 78.8 μm, a SPAN of 1.64, a w / l of 0.81, and a SPHT of 0.84, and after each addition, the mixture was mixed at 300 rpm for 10 minutes under slight reduced pressure (950 mbar). The resulting paste was then homogenized again at 300 rpm for 10 minutes under slight reduced pressure (950 mbar). Component A of the present invention was obtained, having a content of 55.5 vol% of the silicon particles of the present invention and a total content of 73.1 vol% of the thermally conductive filler. The paste composition had a content of 2.25 g / cm³. 3 The density at a shear rate D = 10 s -1 It has a dynamic viscosity of 59 mPa·s at 25°C and a thermal conductivity of 3.3 W / mK, and is therefore very suitable as a gap filler.

[0230] Production of Component B

[0231] In a commercial Labopto planetary mixer (PC Laborsystem GmbH, Maislacherstrasse 6, 4312 Magden, Switzerland) equipped with two rod stirrers and a stripper, 106.5 g of vinyl dimethylsiloxy-terminated polydimethylsiloxane with a viscosity of 120 mPa·s and 9.0 g of a copolymer composed of dimethylsiloxy, methylhydrosiloxy and trimethylsiloxy units with a viscosity of 200 mPa·s and a Si-bonded hydrogen content of 0.18 wt% were mixed for 5 minutes at room temperature and a stirrer speed of 300 rpm. 306.0 g of DAW-05 spherical alumina (available from Denka Company Limited, Nihonbashi Mitsui Tower, 1-1, Nihonbashi-Muromachi 2-chome, Chuo-ku, Tokyo 103-8338, JAPAN) was added and homogenized at 300 rpm for 10 minutes under slight reduced pressure (950 mbar). Subsequently, a total of 574.0 g of the silicon powder of this invention, having an X50 of 78.8 μm, a SPAN of 1.64, a w / l of 0.81, and a SPHT of 0.84, was added in two portions (part 1: 382.7 g, part 2: 191.3 g), and mixed at 300 rpm for 10 minutes under slight reduced pressure (950 mbar) after each addition. The resulting paste was then homogenized again at 300 rpm for 10 minutes under slight reduced pressure (950 mbar). Component B of the present invention is obtained, which has a content of 55.5% by volume of silicon particles of the present invention and a total content of 73.1% by volume of thermally conductive filler. This paste composition has a content of 2.25 g / cm³. 3 The density at a shear rate D = 10 s -1 It has a dynamic viscosity of 37,900 mPa·s at 25°C and a thermal conductivity of 3.7 W / mK, and is therefore very suitable as a gap filler.

[0232] Production of molded parts

[0233] The crosslinked sample of the present invention was prepared by uniformly mixing 1 part by weight of component A and 1 part by weight of component B of the present invention, followed by vulcanization according to the general method GM1. The resulting molded body has a Shore A hardness of 1.4. Example 16 yielded a UL94 V-0 classification. This composition is very suitable for use as a gap filler.

Claims

1. A crosslinkable, thermally conductive silicone composition (Y), comprising... 5-50% by volume of crosslinkable silicone composition (S), and 50-95% by volume of at least one thermally conductive filler (Z), said thermally conductive filler (Z) having a thermal conductivity of at least 5 W / mK, provided that The crosslinkable thermally conductive silicone composition (Y) has a thermal conductivity of at least 0.6 W / mK, and At least 20% by volume of metallic silicon particles present as thermally conductive filler (Z) satisfy the following characteristics: a) Their average diameter x50 is in the range of 30-150 μm; b) They are primarily circular, and are characterized by The width-to-length ratio (aspect ratio w / l) must be at least 0.76; c) Their distribution range SPAN((x90-x10) / x50) is at least 0.40; d) They contain up to 1.5% by weight of silicon particles smaller than 2 µm. The silicon metal particles (Z) have a sphericity value of at least 0.75 (SPHT), and The phrase "primarily spherical" should be understood to refer to silicon particles with spherical to elliptical shapes and smooth surfaces.

2. The crosslinkable silicone composition (Y) according to claim 1, characterized in that, The crosslinkable silicone composition (S) is an addition-crosslinked silicone composition.

3. The crosslinkable silicone composition (Y) according to claim 1 or 2, characterized in that, It contains at least 25% by volume of metallic silicon particles as thermally conductive filler (Z).

4. The crosslinkable silicone composition (Y) according to claim 1 or 2, characterized in that, In addition to the aforementioned metallic silicon particles, it contains only one or two other thermally conductive fillers (Z).

5. The crosslinkable silicone composition (Y) according to claim 1 or 2, characterized in that, The average diameter x50 of the silicon metal particles is in the range of 40-130 µm.

6. The crosslinkable silicone composition (Y) according to claim 1 or 2, characterized in that... It has a thermal conductivity of at least 0.8 W / mK.

7. The crosslinkable silicone composition (Y) according to claim 1 or 2, characterized in that, In each case, at a shear rate D = 10 s -1 At 25°C, it has a dynamic viscosity of 1000–750,000 mPa·s.

8. A method for preparing a crosslinkable silicone composition according to any one of claims 1 to 7, wherein the composition is prepared by mixing the components.

9. A silicone product that can be obtained by dispensing or applying and then curing a crosslinkable silicone composition according to any one of claims 1 to 7.

10. Use of the crosslinkable silicone composition according to any one of claims 1 to 7 as a gap filler, thermal pad, thermal adhesive or encapsulation compound.

11. The use according to claim 10, which is used as a gap filler in a lithium-ion battery for an electric vehicle.

Citation Information

Patent Citations

  • Resin composition and insulation heat conductive sheet

    JP2019131669A

  • Electromagnetic wave absorbing, heat conductive silicone rubber compositions

    US20010051673A1

  • Thermal interface material having spheroidal particulate filler

    US20060228542A1

  • Highly heat conductive silicone rubber composition

    US20070117920A1

  • Heat fixing roll and fixing belt

    US20070135555A1